TO DESIGN THE TECHNOLOGICAL COMBINATIONS AND FED BATCH APPROACH FOR BIOTRANSFORMATION OF PHENOL TO L-TYROSINE WITH RESTING CELLS OF CITROBACTER FREUNDII MTCC 2424 - V, Kumari (Innovare Journal of Life Sciences, 2018)
Â Objective: The study was carried out with an objective to design technological combinations and fed batch approach for improved production of therapeutically and industrially important molecule L-tyrosine. Methods: Technological combinations (23) were designed with optimized chemical parameters for the biotransformation of phenol to L-tyrosine with resting cells of C. freundii MTCC 2424. Eight combinations were obtained by combination of varying three optimized chemical parameters (ammonium chloride, phenol and sodium pyruvate). To observe the effect of phenol on L-tyrosine biosynthesis, two fed batch experiments were designed on the basis of its concentrations. The L-tyrosine formed was detected and quantified by HPLC technique. Results: Maximum L-tyrosine conversion in technological combinations was observed with lower concentration of phenol than optimized value. In fed batch studies, higher phenol concentration was found to be inhibitory for L-tyrosine synthesis due to phenol inactivation of catalyst. Conclusion: The present approach is helpful in comparing the fermentation processes and designing of better bioprocesses. Production of L-tyrosine at minimum cost and energy is helpful in meeting the challenging need of various industries.